Impact of Sales Force and Training Hours on Sales Performance: A Case Study of PT. X's Retail Department - Yotapditya, Igor; Sibarani, Mentiana (Majalah Ilmiah Bijak, 2024)
This study evaluates how sales staff and training hours affect PT.X's retail sales performance from March 2021 to June 2023. The quantitative time series analysis shows that both variables significantly affect monthly gross merchandise value (GMV), with training hours having a greater effect. The regression study shows that each salesperson and training hour improve GMV by IDR 17,890,000 and IDR 168,189,000. The R ² value of 0.645 emphasises the significance of sales training, as well-trained staff can improve sales outcomes and maintain performance during workforce reductions. Strategic managerial decision-making requires a balanced strategy that prioritises quality training to optimise sales success. Future research should consider additional factors such as market conditions and customer satisfaction for a comprehensive understanding.